Effect Of Intraoperative Erector Spinae Block For Faster Recovery And Reduced Post-Operative Pain In Patients Undergoing Discectomies & Spinal Decompression - Arham Azizi; Athar Muniruddin Siddiqui; Naseem Munshi; Muhammad Salman Masroor; Zahra Salahuddin; Muhammad Hassan (Journal of Rawalpindi Medical College)
Objective: To evaluate the efficacy of intraoperative Erector Spinae Block (ESB) in reducing postoperative pain and facilitating recovery in patients undergoing spinal surgeries.